Reflections on the Events of My Life - Fadahunsi, Samuel Olatunde (Nigeria, 2010)
This book records vividly S.O. Fadahunsi's childhood years and educational exploits which demonstrate his ability to prevail as an outstanding pioneer developer and water engineer...
Keywords: Biography & Autobiography; Non-Fiction; Samuel Olatunde Fadahunsi